Feeding habits of Gobiopterus brachypterus (Gobiiformes: Oxudercidae) in Ranu Grati Lake, East Java, Indonesia and their relationship with food availability - SEPTI ANITASARI; DIANA ARFIATI; SUSILO SUSILO; AGUNG PRAMANA WARIH MARHENDRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anitasari S, Arfiati D, Susilo, Marhendra APW. 2024. Feeding habits of Gobiopterus brachypterus (Gobiiformes: Oxudercidae) in Ranu Grati Lake, East Java, Indonesia and their relationship with food availability. Biodiversitas 25: 2925-2936. Ranu Grati, a volcanic lake located in Pasuruan District, East Java, Indonesia, is home to the endemic Gobiopterus brachypterus (Bleeker 1855) locally known as the lempuk fish. This research aims to elucidate the feeding habits of G. brachypterus and their relationship with food availability in Ranu Grati. The study investigates the food ecology of including their diet composition, habitat preferences, and feeding habits in relation to natural food availability including plankton abundance, relative abundance, uniformity index, dominance index plankton sampling was conducted at five stations by with the samples preserved in formalin and concentrated in the lab for analysis under a microscope. Fish were also collected at these stations using random sampling, dissected in the field, and their digestive tracts were preserved and later examined microscopically to identify the food types down to the lowest taxonomic level. The results reveal that the phytoplankton community in Ranu Grati Lake includes nine classes: Bacillariophyceae, Chlorophyceae, Cyanophyceae, Coscinodiscophyceae, Trebouxiophyceae, Dinophyceae, Zygnematophyceae, Raphidophyceae, and Euglenoidea. The zooplankton community comprises four classes: Monogononta, Copepoda, Branchiopoda, and Tubulinea. Phytoplankton in Ranu Grati Lake exhibit high diversity, with a diversity index of 3.739, and high uniformity, indicated by an evenness index of 0.957, showing no dominance (dominance index: 0.115). In contrast, zooplankton demonstrate moderate diversity (diversity index: 2.528), moderate evenness (evenness index: 0.647), and similarly show no dominance (dominance index: 0.216). The relative lengths of the intestines of G. brachypterus. are 0.163 and 0.132, indicating a carnivorous diet. The index of preponderance values highlights that Bacillaria sp., Oscillatoria sp., Microcystis sp., Oocystis sp., and Volvox sp. are significant dietary components for G. brachypterus, whereas Pinnularia sp., Entomoneis sp., Cymbella sp., Thalassiosira sp. and others contribute minimally or are absent. This highlights the dietary preferences of G. brachypterus. The stomach contents confirm that G. brachypterus exhibit a preference for phytoplankton, demonstrating opportunistic, carnivorous feeding behavior based on the availability of food in their natural environment.